Evaluation of carcinoembryonic antigen (CEA), epidermal growth factor receptor (EGFR), epithelial cell adhesion molecule EpCAM (GA733-2), and carbohydrate antigen 19-9 (CA 19-9) levels in colorectal cancer patients and correlation with clinicopathological - Mourtzikou,A.; Stamouli,M.; Kroupis, C.; Christodoulou, S.; Skondra,M.; Kastania, A; Pectasides, D.; Athanasas, G.; Dimas, C (Clin.Lab, 2012)
BACKGROUND: Colorectal cancer (CRC) is a major public health problem and one of the leading causes of death worldwide. The aim of our study was: a) to determine the CEA, CA 19-9, EGFR, and EpCAM (GA733-2) levels both in healthy volunteers and in colorectal cancer patients, b) to evaluate the ELISA method for EGFR and EpCAM (GA733-2) measurement, and c) to correlate the tumor marker levels with clinicopathological findings in the CRC patients group. METHODS: Our study was conducted on 50 blood samples obtained from CRC patients and 40 blood samples from healthy individuals. CEA and CA 19-9 measurements were performed using electrochemiluminescence immune-assay technology, while EGFR and EpCAM (GA733-2) measurements were performed by an in-house enzyme immunoassay. RESULTS: CEA, CA 19-9, and EpCAM (GA733-2) levels were higher in the CRC patients group than in the control group. EGFR levels were lower in the patients group than in the control group. The mean levels of CA 19-9 and EpCAM (GA733-2) vary at different colon cancer stages. CEA, CA19-9, and EpCAM (GA733-2) vary according to performance status. CONCLUSIONS: CEA, CA 19-9, and EpCAM (GA733-2) showed similar specificity (80%, 80% and 84%, respectively). EGFR showed the lowest sensitivity and specificity. CA 19-9 was the marker with the highest sensitivity. The need for convenient tumour marker tests with high sensitivity is of great importance for early diagnosis and monitoring of CRC
DA - 20120712 IS - 1433-6510 (Print) IS - 1433-6510 (Linking) LA - eng PT - Journal Article RN - 0 (Antigens, Neoplasm) RN - 0 (Biomarkers, Tumor) RN - 0 (CA-19-9 Antigen) RN - 0 (Carcinoembryonic Antigen) RN - 0 (Cell Adhesion Molecules) RN - 0 (EPCAM protein, human) RN - EC 2.7.10.1 (EGFR protein, human) RN - EC 2.7.10.1 (Receptor, Epidermal Growth Factor) SB - IM
Keywords: Adult; Antigens,Neoplasm; Biomarkers; Biomarkers,Tumor; Blood; CA-19-9 Antigen; Carcinoembryonic antigen; Cell adhesion molecules; classification; Colorectal Neoplasms; Diagnosis; Electrochemical Techniques; Enzyme-Linked Immunosorbent Assay; Female; Greece; Humans; Immunoassay; Male; methods; Middle Aged; Neoplasm Staging; pathology; Receptor,Epidermal Growth Factor; Sensitivity and Specificity